A Taguchi-Based Optimization of Ultrasound-Assisted Electrocoagulation Use of Aluminum Electrodes for Laundry Wastewater Treatment: Environmental Engineering - Anjasmoro; Parmadi, Faris Achmad; Wulandari, Amalia; Aurelia , Rafa Hasna; Valentine, Erinda Aulia; Arifin, Zainal (Al-Kimia, 2025)
Sono-electrocoagulation (SEC) has emerged as an effective and eco-friendly hybrid process for the treatment of laundry wastewater containing surfactants and microfibers. In this research, the Taguchi experimental design (L9 orthogonal array) was employed to optimize the operating parameters of the SEC process using aluminum electrodes. The factors investigated were electrocoagulation time (10, 20, and 30 min) and electrode distance (2, 3, and 4 cm). The response variables considered were the percentage removal of surfactants and microfibers, analyzed using the larger-is-better signal-to-noise ratio criterion. The results demonstrated that the sono-electrocoagulation process significantly reduced the concentration of pollutants. The surfactant concentration decreased from 3.46 mg/L to 0.334 mg/L, while the microfiber weight decreased from 0.096 g to 0.011 g. The Taguchi optimization revealed that the optimum operating condition occurred at an electrocoagulation time of 30 minutes and an electrode distance of 3 cm, achieving 90.35% surfactant removal and 88.54% microfiber removal. Based on the analysis of variance, the most influential factor on pollutant removal efficiency was electrode distance, followed by electrocoagulation time. This research highlights the potential of the Taguchi-based optimization approach to improve sono-electrocoagulation performance in laundry wastewater treatment, demonstrating its ability to effectively eliminate both chemical and physical pollutants.